Making Freedom Irresistible- An Application of the ‘Game Theory’ and ‘Inspiration Economy Theory’ on Pro-Palestine Boycott Movements after War on Gaza 2023-2025 - Mohamed Buheji (Utilitas Mathematica, 2025)
Classical Game Theory reveals a world of strategic traps, where rational self-interest leads to sub-optimal collective outcomes, as seen in the enduring Israeli-Palestinian conflict and specifically during the War on Gaza 2023-2025. This paper explores how the Inspiration Economy (IE) theory provides the key to mitigating these traps. The researcher posit that IE acts as a "meta-game," fundamentally altering the strategic landscape by introducing new payoffs—such as purpose, trust, and belonging—and fostering a collective identity where individual, group and community success align. Through reviewing the outcome of the Gaza Resilience Lab, besides an analysis of the global boycott and BDS movements, the paper demonstrates how a purely punitive, game-theoretic model can be transformed into a positive-sum, sustainable, inspirational force. Then, the research simulates applying the IE theory principles to reframe the win condition, expanding the player base, and leveraging narrative, thus the movement for Palestinian rights can evolve from a reaction to oppression into a proactive, visionary campaign that attracts global support by offering a win-win-win future for Palestinians and their supporters. This synthesis demonstrates a "rational" strategy in a complex, interconnected world where collaboration and inspiration become the most rewarding moves. By shifting the payoffs to include moral currency, fostering a collective identity, and articulating a compelling vision of the future, the movement can make the old game of Israeli occupation unsustainable and the new game of freedom and justice irresistible. This framework offers a transformative strategy for not only the Palestinian struggle but for modern activism and conflict resolution as a whole.Keywords: War on Gaza, Inspiration Economy Theory, Game Theory, Prisoner's Dilemma, Gaza Resilience Lab, Boycott, BDS, Pro-Palestine Movement, Consumer Activism, Asymmetric Conflict, Value Co-creation, Transformative Strategy, Collective Identity